The Impact of World Bank-Assisted Projects on Poverty Alleviation - Herbert, Eti; Odeniyi, Omolara Olateju (Consilience, 2022)
The World Bank is an international financial institution responsible for issuing loans, grants, aids, etcetera to states and multinational corporations for the purpose of carrying out reconstruction and development projects and investments, respectively. Several criticisms have trailed the World Bank’s project financing, especially with regards to the conditionality of economic restructuring usually imposed thereto. However, in 2013, the World Bank realigned its goal toward reducing poverty to less than 3 percent by 2030. Mechanisms such as the Poverty Reduction Strategic Paper (PRSP), Compliance Advisor Ombudsman (CAO) were created toward this end. It is in view of the foregoing that this paper examined the impact of World Bank assisted projects on poverty alleviation. This paper concluded that for the Bank to achieve its goal at the set date, a purposive approach must be adopted to ensure the participation of the various stakeholders in the poverty alleviation process.